Air transport liberalisation and airport dependency: developing a composite index. (January 2016) - Koo, T.; Halpern, N.; Papatheodorou, A.; Graham, A.; Arvanitis, P.
Highlights: A composite Gini-based index is developed to measure airport dependency. Dependency is measured according to market, spatial and temporal concentration. Data is collected and analysed over a ten year period from 2005 to 2014. 735 European airports are compared. Implications for impact/added value analysis are considered. Abstract: Air transport liberalisation in Europe has produced some major changes to the networks operated by airlines and the services available at airports. Within this context the degree of airport dependency in terms of market, spatial and temporal concentration is important to know from an economic geography and risk management perspective. A composite index called the Airport Dependency Index (ADI) is developed to measure airport dependency based on the concept of the relative Gini coefficient. Liberalisation has had varying impacts depending on the size and type of airport and so a comparison is made of the degree of dependency at a large sample of European airports using the ADI. The ADI has the potential to provide insight on the sustainability and worthiness of financing airport projects, and on whether airports should diversify further their activities by investing in the growth and expansion of their network.